Improving the value of cull cows through antemortem management practices and postmortem enhancement technologies - Hutchison, Shanna (Kansas State University, 2007)
Sixty cows were utilized to investigate the use of zilpaterol, implanting, and concentrate feeding on performance, carcass traits, subprimal yield, steak retail display, and meat palatability of cows fed for 70 d. The 5 treatments were: 1) grass-fed on pasture (Grass); 2) concentrate-fed (C); 3) concentrate-fed and implanted (CI) with a trenbolone acetate/estradiol implant, DE); 4) concentrate-fed and fed zilpaterol beginning on d 38 of the feeding period (CZ); and 5) concentrate-fed, implanted and fed zilpaterol (CIZ). Hot carcass weights and dressing percentages were higher (P < 0.05) for all concentrate-fed cows than grass-fed cows. The CIZ cows had the largest and grass-fed cows the smallest longissimus muscle (LM) areas. Total subprimal weights were lightest for cuts from the grass-fed cows; and CIZ cows had greater weights than those from C cows. Sensory panelists found LM steaks from C and grass-fed cows were more tender than steaks from CZ and CIZ cows; and steaks from CI cows were more tender than steaks from CIZ cows. However, no tenderness differences were observed among treatments for knuckle (KN) steaks. In another study, carcasses from 31 fed cows and 24 fed steers were used to investigate the effects of aging (7 or 28 d) on LM retail display; aging and enhancement (blade tenderization and enhancement solution injection) on LM tenderness; and aging on enhanced KN, top blade, and top sirloin steaks. Steaks (LM) aged 7 d had less discoloration and were more color stable than steaks aged for 28 d. A sensory panel found enhanced-cow LM steaks were more tender than non-enhanced steaks; and aging for 28 d improved tenderness compared to 7 d aging for non-enhanced steaks only. Aging for 28 d compared to 7 d improved Warner-Bratzler shear (more tender) for enhanced cow top sirloin, steer top sirloin, and steer top blade steaks. Feeding cull cows a concentrate diet improved lean meat yields. When feeding a concentrate diet a combination of an implant and feeding zilpaterol can further increase lean meat yields. Enhancement provides an opportunity to improve tenderness of steaks from fed cows and steers.
Keywords: Cows; Beta Agonist; Implants; Aging; Tenderness; Enhancement; Agriculture, Food Science and Technology (0359)